Rancang Bangun Sistem Pemilahan Lele Otomatis dan Pengaruh Dimmer Terhadap Debit Pompa Air - Alif Aditya Darmawan; Khilda Afifah; Istiqomah (Jurnal Serambi Engineering, 2024)
Manual sorting of catfish is a labour-intensive process in catfish farming, requiring considerable time and effort. Therefore, an effective and user-friendly automated catfish grading system is required. Currently, several automated sorting systems have been developed using load cells, but these methods are inefficient as they require fish to be sorted one at a time. The method used in this system is similar to the concept of a coin sorter, where catfish flow through holes of different diameters according to their head size. In addition, the system uses a water pump to circulate water from the final storage tank back to the holding tank to help guide the fish to the sorting channel. The water flow rate of the pump can be adjusted using a dimmer, which works by limiting the voltage used by the pump. Testing of the grading system was carried out under two conditions, grading fish of the same size range and grading fish of a significantly different size range. The results showed that sorting fish of the same size range had a higher accuracy (86.1%) compared to sorting fish of a different size range (61.9%). An analysis of the effect of the dimmer on the pump was also carried out, showing that the dimmer can effectively control the water flow rate.